Insider trading and financing constraints - Ataullah, Ali; Goergen, Marc; Le, Hang (Wiley, 2014)
Insider trading may alleviate financing constraints by conveying value‐relevant information to the market (the information effect) or may exacerbate financing constraints by impairing market liquidity and distorting insiders’ incentives to disclose value‐relevant information (the confidence effect). We examine the significance of these two contrasting effects by investigating the link between insider trading and financing constraints as measured by the investment‐cash flow sensitivity. We find that, overall insider trading exacerbates financing constraints; however the information effect dominates the confidence effect for insider purchases. Only trades by executive directors are significantly related to financing constraints.